Exploitation of Polymorphic Sequences in Chloroplast Genome for Identification of Commercial Tobacco Cultivars: Fingerprinting of Tobacco Cultivars with Cp DNA Marker - Khan, Muhammad Ramzan; Ajmal, Wajya; Ur Rehman, Obaid; Aqeel, Muhammad; Muhammad Ali, Ghulam (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Tobacco is an important commercial commodity. Discrimination of tobacco cultivars at DNA level is extremely important for selling of brand, free of mixing. Chloroplast markers have sufficient resolving power for differentiation at intra-varietal level. In this study only chloroplast genome markers were used to amplify polymorphic regions encoding genes involved in photosynthetic machinery of plants. This region encompassing 9000 to 9600bp harbors SNPs, Indels and SSRs. Different bioinformatics and phylogenetic software were used to investigate relationship of DNA sequences of 11 unknown plant samples with a reference sequence from NCBI. Multiple alignments exhibited sequence conservation encompassing a substantial region. But it also revealed important variety specific SNPs. Sequence similarity index was generated for grouping of unknown plants. The unidentified plants were differentiated into different clusters as revealed by phylogenetic analysis. Furthermore, a neighbor-net network analysis validated the results of Neighbor Joining tree. Our analysis indicates that there exist at least 5 varieties of tobacco. The V1 is the most distant cultivar. V5 is also separated from the rest of cultivars. But V2, V3 and reference sequence make further linage, and can be considered as separate clade. A bigger cluster including V7, S2 and V6 is differentiated into distinct group. The S1, V9, V10 and V8 are the 5th cluster that can be considered as a single variety. Hence there were 5 varieties in total that were mixed in 11 samples.